Immunoediting and Antigen Loss: Overcoming the Achilles Heel of Immunotherapy with Antigen Non-Specific Therapies - Monjazeb, Arta M.; Zamora, Anthony E.; Grossenbacher, Steven K.; Mirsoian, Annie; Sckisel, Gail D.; Murphy, William J. (Frontiers in Oncology, 2013)
Cancer immunotherapy has emerged as a mainstream therapy option in the battle against cancer. Pre-clinical data demonstrates the ability of immunotherapy to harness the immune system to fight disseminated malignancy. Clinical translation has failed to recapitulate the promising results of pre-clinical studies although there have been some successes. In this review we explore some of the shortcomings of cancer immunotherapy that have limited successful clinical translation. We will give special consideration to what we consider the most formidable hurdle to successful cancer immunotherapy: tumor induced immune suppression and immune escape. We will discuss the need for antigen specific immune responses for successful immunotherapy but also consider the need for antigen specificity as an Achilles heel of immunotherapy given tumor heterogeneity, immune editing, and antigen loss. Finally, we will discuss how combinatorial strategies may overcome some of the pitfalls of antigen specificity and highlight recent studies from our lab which suggest that the induction of antigen non-specific immune responses may also produce robust anti-tumor effects and bypass the need for antigen specificity.